2021
DOI: 10.3390/curroncol28050319
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Duodenobiliary Reflux-Related Dysfunction of Covered Biliary Metal Stents after Treatment of Duodenal Stricture in Patients with Malignant Biliary and Duodenal Obstruction

Abstract: Duodenal obstruction is often accompanied with unresectable malignant distal biliary obstruction in patients who have undergone biliary self-expandable metal stent (SEMS) placement. Duodenobiliary reflux (DBR) is a major cause of recurrent biliary obstruction (RBO) after covered biliary SEMS placement. We analyzed the risk factors for DBR-related SEMS dysfunction following treatment for malignant duodenal obstruction. Sixty-one patients with covered SEMS who underwent treatment for duodenal obstruction were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A retrospective study assessing patients who underwent double stenting showed that duodenal stent dysfunction and the biliary stent end located above the duodenal stent were risk factors for biliary stent dysfunction (89). A similar study by Taiwanese researchers reported that duodenal obstruction below the papilla and a score of ≤2 on the GOOSS (20) after treatment for duodenal obstruction were associated with DBR-related biliary CSEMS dysfunction (90). More attention should be paid to formulating a treatment strategy for patients with combined biliary and duodenal obstruction, considering the possible risk of developing DBR.…”
Section: Choice Of Biliary Intervention In Cases With Coexisting Bili...mentioning
confidence: 96%
“…A retrospective study assessing patients who underwent double stenting showed that duodenal stent dysfunction and the biliary stent end located above the duodenal stent were risk factors for biliary stent dysfunction (89). A similar study by Taiwanese researchers reported that duodenal obstruction below the papilla and a score of ≤2 on the GOOSS (20) after treatment for duodenal obstruction were associated with DBR-related biliary CSEMS dysfunction (90). More attention should be paid to formulating a treatment strategy for patients with combined biliary and duodenal obstruction, considering the possible risk of developing DBR.…”
Section: Choice Of Biliary Intervention In Cases With Coexisting Bili...mentioning
confidence: 96%
“…Thus, one of the main reasons for cholangitis being one of the most serious complications of minimally invasive BD decompression techniques, is stent occlusion, which is strongly associated with duodenobiliary reflux. Therefore, avoidance of duodenobiliary reflux is important in preventing stent dysfunction and cholangitis onset[ 23 ].…”
Section: Introductionmentioning
confidence: 99%